FTO variant, energy intake, physical activity and basal metabolic rate in Caucasians. The HAPIEE study - Hubáček, Jaroslav; Pikhart, Hynek; Peasey, A; Kubínová, Růžena; Bobák, Martin (Physiological research, 2011)
The FTO gene variants are the most important genetic determinants of body weight and obesity known so far, but the mechanism of their effect remains unclear. We have analyzed FTO rs17817449 variant (G>T in first intron) in 6024 adults aged 45-69 years to assess the potential mediating role of diet and physical activity. Diet was assessed by a 140-item food frequency questionnaire. Physical activity was measured by hours spent during a typical week by sport, walking and other activities outside of work requiring heavy and medium physical activity. Basal metabolic rate was calculated according Schofield formula. The FTO variant was significantly associated with body mass index (means in GG, GT and TT carriers were 28.7, 28.2 and 27.8 kg/m(2), p<0.001) and basal metabolic rate (BMR) (means in GG, GT and TT were 1603, 1588 and 1576 kcal per day, respectively, p<0.008) but it was not associated with physical activity, total energy intake or with energy intakes from fat, carbohydrates, proteins or alcohol. Results were essentially similar in men and women and the adjustment for physical activity or dietary energy intake did not reduce the effect of the FTO polymorphism. Means of BMR per kg of body weight was lowest in GG carriers (20.09, 20.21 for GT and 20.30 for TT, p<0.006) and this effect was more pronounced in females. These results suggest that the effect of the FTO rs17817449 variant on BMI in Caucasian adults is not mediated by energy intake or physical activity, but some effect on BMR per kg of body weight is possible.
Keywords: index tělesné hmotnosti; Humans; běloši; lidé středního věku; Middle Aged; Exercise; Proteins; Financing, Organized; složení těla; Body Mass Index; financování organizované; Basal Metabolism; mužské pohlaví; proteiny; Energy Intake; cvičení; Body Composition; ženské pohlaví; bazální metabolismus; White People; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; Male; energetický příjem; Female